Optimization of electrical conductivity in the Na2O-P2O5-AlF3-SO3 glass system - Le, Quyen H.; Calahoo, Courtney; Xia, Yang; Buchheim, Johannes; Bragatto, Caio B.; Wondraczek, Lothar (Journal of the American Ceramic Society, 2020)
We report on the individual roles of charge carrier density and network modification in sodium ion conducting glasses from the Na2O-P2O5-SO3-AlF3 (NAPFS) system. For this, a broad range of glass compositions was considered across the series of 44Na2O/(56 – x − y)P2O5/xAlF3/ySO3, 47Na2O/(53 − x − y)P2O5/xAlF3/ySO3, and 50Na2O/(50 − x − y)P2O5/xAlF3/ySO3, with x = 8, 12, 16, 20 and y = 0, 5, 7, 10, 12. Impedance spectroscopy was conducted on these glasses at frequencies from 10−2 to 106 Hz and over temperatures from 50 to 250°C, and complemented by structural analyses using Raman spectroscopy and nuclear magnetic resonance data. While the trends in dc conductivity and activation energy follow that of Na2O content (increasing from 44 to 50 mol%), substantial enhancement of conductivity (by about two orders of magnitude) and correspondingly lower activation energy were also found for constant Na2O concentration when adjusting SO3 or AlF3 within specific limits of glass structure.
CRIS-Team Scopus Importer:2023-04-20
Keywords: electrical conductivity; electrolyte; glass; impedance spectroscopy; ionic conductivity